MANTLE STRUCTURE AND RIFTING PROCESSES IN THE BAIKAL-MONGOLIA REGION: GEOPHYSICAL DATA AND EVIDENCE FROM XENOLITHS IN VOLCANIC ROCKS - Ionov D. (My University, 2002)
The origin of the Baikal rift zone (BRZ) has been debated between the advocates of passive and active rifting since the 1970s. A re-assessment of the relevant geological and geophysical data from Russian and international literature questions the concept of broad asthenospheric upwelling beneath the rift zone that has been the cornerstone of many “active rifting” models. Results of a large number of early and recent studies favour the role of far-field forces in the opening and development of the BRZ. This study emphasises the data obtained through studies of peridotite and pyroxenite xenoliths brought to the surface by alkali basaltic magmas in southern Siberia and central Mongolia. These xenoliths are direct samples of the upper mantle in the vicinity of the BRZ. Of particular importance are suites of garnet-bearing xenoliths that have been used to construct P–T- composition lithospheric cross-sections in the region for the depth range of 35–80 km.